Peningkatan Pemahaman Tentang Pengelolaan Dan Penyusunan Laporan Keuangan Desa Pada Siswa Siswi SMK Muhammadiyah Larangan Kabupaten Brebes - Nurul Mahmudah; Yusri Anis Faidah; Erni Unggul Sedya Utami; Andri Widianto (Annusfy : Journal of Multidisciplinary Research, 2026)
The community service activity aims to enable students of Muhammadiyah Larangan Vocational School, Brebes Regency to improve their understanding of village financial management and reporting. This community service was attended by 30 12th grade students. The methods used in this community service activity include lectures and discussions, as well as a community service team conducting surveys and direct observations at the location to collect initial data. The results of this community service activity are that students are able to understand both theoretically and in the field (village) about village financial management obtained from the results of discussions and questions and answers.about village financial management obtained from the results of discussions and questions and answers.